2009
DOI: 10.1111/j.1540-4781.2009.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Learners' Beliefs About Grammar Instruction and Error Correction

Abstract: Learner beliefs are an important individual difference in second language (L2) learning. Furthermore, an ongoing debate surrounds the role of grammar instruction and error correction in the L2 classroom. Therefore, this study investigated the beliefs of L2 learners regarding the controversial role of grammar instruction and error correction. A total of 754 L2 students at an American university completed a questionnaire consisting of 37 Likert-scale items and 4 openended prompts. The quantitative items were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
147
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(174 citation statements)
references
References 38 publications
10
147
2
4
Order By: Relevance
“…Other studies showed that learners' epistemological beliefs (i.e., beliefs about the nature of learning) differ from those about language learning (Mori, 1999), suggesting that learners perceive learning in general differently from learning about specific subjects and concepts. Loewen et al (2009), for example, showed that learners view grammar instruction and CF as distinct categories, and the authors have called for future research to consider this differentiation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies showed that learners' epistemological beliefs (i.e., beliefs about the nature of learning) differ from those about language learning (Mori, 1999), suggesting that learners perceive learning in general differently from learning about specific subjects and concepts. Loewen et al (2009), for example, showed that learners view grammar instruction and CF as distinct categories, and the authors have called for future research to consider this differentiation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schulz's (1996Schulz's ( , 2001) questionnaire on teacher and learner attitudes about the role of grammar study and CF in FL learning, for example, contained a mere seven questions on the role of CF in language learning, of which four dealt with the role of feedback in general, two with students' attitudes toward feedback on written errors, and only one with learners' attitudes toward oral CF. Similarly, Loewen et al (2009) used a 37-item Likert-scale questionnaire with four openended prompts to investigate the beliefs of 754 L2 and FL learners about the role of grammar instruction and error correction. Their questionnaire focused primarily on the role, efficacy, and importance of grammar, thus giving error correction lesser weight.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Schulz (1996) explored on this subject and conducted a pioneering research at University of Arizona, before reporting that discrepancies were most noticeable on the questions of error correction, the least agreement was on the desirability of correcting written mistakes, while the highest disagreement was found on the desirability of correcting oral mistakes. (ibid: 346) S. Loewen et al (2009) investigated a group of learners studying different target languages, such as French, Latin, Spanish etc, and revealed their different attitudes over the role of grammar instruction and error corrections and found that they were varied. Nuriye and Selami (2017:37-51) fixed their attention on speaking class, however, and surveyed the teachers' understanding and recognition of error correction before summarizing the strategies that the teachers employed in correction.…”
Section: Previous Studiesmentioning
confidence: 99%